2021
DOI: 10.1681/asn.2020050681
|View full text |Cite
|
Sign up to set email alerts
|

Copy Number Variant Analysis and Genome-wide Association Study Identify Loci with Large Effect for Vesicoureteral Reflux

Abstract: BackgroundVesicoureteral reflux (VUR) is a common, familial genitourinary disorder, and a major cause of pediatric urinary tract infection (UTI) and kidney failure. The genetic basis of VUR is not well understood.MethodsA diagnostic analysis sought rare, pathogenic copy number variant (CNV) disorders among 1737 patients with VUR. A GWAS was performed in 1395 patients and 5366 controls, of European ancestry.ResultsAltogether, 3% of VUR patients harbored an undiagnosed rare CNV disorder, such as the 1q21.1, 16p1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
19
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5
4

Relationship

2
7

Authors

Journals

citations
Cited by 18 publications
(20 citation statements)
references
References 96 publications
(124 reference statements)
1
19
0
Order By: Relevance
“…37 In addition, copy number variants have been shown to cause CAKUT in up to 16.6% of cases. [38][39][40] In conclusion, we showed that a likely monogenic cause of CAKUT can be detected using ES and reverse phenotyping in 11.4% of families. We suggest that reverse phenotyping be systematically applied to families with CAKUT to increase the diagnostic yield of molecular genetic diagnostics.…”
Section: Limitations Of Esmentioning
confidence: 63%
“…37 In addition, copy number variants have been shown to cause CAKUT in up to 16.6% of cases. [38][39][40] In conclusion, we showed that a likely monogenic cause of CAKUT can be detected using ES and reverse phenotyping in 11.4% of families. We suggest that reverse phenotyping be systematically applied to families with CAKUT to increase the diagnostic yield of molecular genetic diagnostics.…”
Section: Limitations Of Esmentioning
confidence: 63%
“…In particular, CNV genotyping was crucial in studies involving diseases such as schizophrenia [ 216 , 217 ], bipolar disorder [ 216 ], Parkinson’s disease [ 218 ], Autism Spectrum Disorder [ 219 ] and attention deficit hyperactivity disorder [ 220 ]. Other CNVs studies included different outcomes such as HBV [ 221 , 222 ], autophagy [ 223 ], gallstones disease [ 224 ], vesicoureteral reflux [ 225 ], esotropia [ 226 ], cheap screenings for primary immunodeficiency [ 227 ] and COVID-19 potential targets [ 228 ]. For these studies, PennCNV was the most popular, followed by Nexus Copy Number, Birdsuite and QuantiSNP.…”
Section: Recent Studies Applying Inference Methods Of Snp Datamentioning
confidence: 99%
“…38 Many common variants associated with specific kidney function measures or complex kidney diseases have been identified through genome-wide association studies (GWAS) and exome-or genome-sequencing studies of large population samplesusually of European or East Asian ancestry (Figure 2). 13,14,17,19,31,[39][40][41] The largest number of locigenomic regions containing associated SNPs-were discovered for the continuous kidney function measure eGFR, with studies based on data from >1 million individuals reporting more than 250 such loci. [12][13][14]17,19,22,23,31,40, Although the distinction of monogenic versus polygenic diseases provides a useful practical framework, genetic risk variants for kidney diseases occur on a spectrum from rare variants with large effects to common variants with small effects, and many diseases do not fit neatly into either category.…”
Section: Table 1 | Summary Points From the Genetics In Ckd Controvers...mentioning
confidence: 99%
“…13,14,17,19,31,[39][40][41] The largest number of locigenomic regions containing associated SNPs-were discovered for the continuous kidney function measure eGFR, with studies based on data from >1 million individuals reporting more than 250 such loci. [12][13][14]17,19,22,23,31,40, Although the distinction of monogenic versus polygenic diseases provides a useful practical framework, genetic risk variants for kidney diseases occur on a spectrum from rare variants with large effects to common variants with small effects, and many diseases do not fit neatly into either category. For example, apolipoprotein L1 (APOL1)associated kidney risk variants are common among some populations of African ancestry and impart a relatively high risk under a recessive mode of inheritance, but these variants are not considered monogenic.…”
Section: Table 1 | Summary Points From the Genetics In Ckd Controvers...mentioning
confidence: 99%